The Expression Dynamics of piRNAs Derived From Male Germline piRNA Clusters and Retrotransposons - Kawase, Masaki; Ichiyanagi, Kenji (Frontiers in Cell and Developmental Biology, 2022)
In mammals, germ cells produce a class of small regulatory RNAs called PIWI-interacting RNAs or piRNAs, which are 25–32 nucleotides in length. The profile of testicular piRNAs changes during development. The piRNAs detected in fetal testes at embryonic day 13.5 and later are called fetal piRNAs. The piRNAs detected in testes in a period where germ cells do not yet enter the pachytene stage of meiotic prophase I are called pre-pachytene piRNAs, whereas those in testes at later postnatal days are called pachytene piRNAs. Here, to elucidate the exact expression dynamics of these piRNAs during development, we compared piRNAs present in male germ cells at different stages, which were purified by fluorescence-activated cell sorting, and those in embryonic testes. The analysis identified three distinct groups of piRNA clusters: prospermatogonial, early, and late clusters. piRNA length was largely correlated with the repertoire of PIWI-like proteins in respective germ cells; however, the late piRNA clusters tended to generate longer (PIWIL1-type) piRNAs, whereas the early clusters tended to generate shorter (PIWIL2-type) piRNAs, suggesting a cluster- or sequence-dependent mechanism for loading onto PIWI-like proteins. Retrotransposon-derived piRNAs, particularly evolutionary young retrotransposons, were abundantly produced in prospermatogonia, however, their abundance declined as development proceeded. Thus, in later stages, retrotransposon-derived piRNAs were not enriched with those from evolutionary young elements. The results revealed that, depending on the piRNA clusters from which they are derived, longer PIWIL1-type piRNAs are produced earlier, and shorter PIWIL2-type piRNAs remain in a longer period, than previously thought.